Small lies? Authenticity and the artist interview - Jean Wainwright (Journal of Art Historiography, 2020)
This paper examines the ethical and art-historical questions that are raised when conversations with artists are edited for sound clips or transcribed for books and catalogues. Should the reader of an interview be aware of how much has been ‘tidied up’ or redacted? Does it matter that what one is reading is a version of the authentic truth of the original?